Determinants of maternal near-miss among women admitted to public hospitals in North Shewa Zone, Ethiopia: A case-control study - Teshome, Hana Nigussie; Ayele, Esubalew Tesfahun; Hailemeskel, Solomon; Yimer, Osman; Mulu, Getaneh Baye; Tadese, Mesfin (Frontiers in Public Health, 2022)
Background: A maternal near-miss (MNM) refers to a woman who presents with life-threatening complications during pregnancy, childbirth, or within 42 days of termination of pregnancy but survived by chance or due to the standard care she received. It is recognized as a valuable indicator to examine the quality of obstetrics care as it follows similar predictors with maternal death. Ethiopia is one of the sub-Saharan African countries with the highest rate of maternal mortality and morbidity. Thus, studying the cause and predictors of maternal near-miss is vital to improving the quality of obstetric care, particularly in low-income countries. Objective: to identify determinants of maternal near-miss among women admitted to public hospitals in North Shewa Zone, Ethiopia, 2020. Methods: A facility-based unmatched case-control study was conducted on 264 women (88 cases and 176 controls) from February to April 2020. Data were collected using pretested interviewer-administered questionnaires and a review of medical records. Data were entered into Epi-data version 4.2.2 and exported to SPSS version 25 for analysis. Variables with a p-value <0.25 in the bivariable analysis were further analyzed using multivariable logistic regression analysis. Finally, variables with a p-value <0.05 were considered statistically significant. Result: Severe pre-eclampsia (49.5%) and postpartum hemorrhage (28.3%) were the main reasons for admission of cases. Educational level of women (AOR = 4.80, 95% CI: 1.78-12.90), education level of husbands (AOR = 5.26; 95% CI: 1.46-18.90), being referred from other health facilities (AOR = 4.73, 95% CI: 1.78-12.55)], antenatal care visit (AOR = 2.75, 95% CI: 1.13-6.72), cesarean section (AOR = 3.70, 95% CI: 1.42-9.60), and medical disorder during pregnancy (AOR = 12.06, 95% CI: 2.82-51.55) were found to significantly increase the risk of maternal near-miss. Whereas, younger age of women significantly decreased the risk of maternal near miss (AOR = 0.26, 95% CI: 0.09-0.75). Conclusion: Age, educational level, antenatal care follow-ups, medical disorder during pregnancy, mode of admission, and mode of delivery were significant predictors of maternal near-miss. Sociodemographic development, use of ANC services, early detection and management of medical diseases, reducing cesarean section, and improving the referral systems are crucial to minimizing the maternal near-miss.